Influence of partial pork meat replacement by pulse flour on physicochemical and sensory characteristics of low-fat burgers - Argel, Natalia Soledad (2020)
Background: Numerous non-meat ingredients, such as hydrocolloids, starches, and fibers, have been studied to improve texture characteristics and increase the ability to bind water in low-fat meat products. In this sense, pulses flours (lentil, chickpea, pea, and bean) were studied at two levels and various water:flour ratios to replace 10–44% pork meat in low-fat burgers and determine the effect on their sensory and technological properties (cooking yield, expressible liquid, diameter reduction, and color and texture profile). Results: All pork-meat burgers that included pulse flour showed higher cooking yields, lower diameter reductions, and expressible liquids than all-meat burgers, which displayed better oil and water retention. Higher water additions resulted in burgers with less hardness. Burgers with 80 g kg−1 lentil flour in all water/flour ratios presented the lowest total color difference (ΔE) compared with the commercial control. Burgers with the higher level of all pulse flour tested and medium water levels showed acceptable sensory scores. Conclusions: Partial pork meat replacement by different legume flour (lentil, chickpea, pea, and bean), at levels of 80 and 150 g kg−1 and water/flour ratios of 1250, 1600, and 2000 g kg−1 resulted in low-fat burgers with adequate physicochemical characteristics. Moreover, the sensorial evaluation of the formulations with the maximum flour addition and intermediate water/flour ratio showed that they had good sensorial acceptability with no effect of flour type.